2017
DOI: 10.1007/s10040-017-1639-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliable yields of public water-supply wells in the fractured-rock aquifers of central Maryland, USA

Abstract: Most studies of fractured-rock aquifers are about analytical models used for evaluating aquifer tests or numerical methods for describing groundwater flow, but there have been few investigations on how to estimate the reliable long-term drought yields of individual hard-rock wells. During the drought period of 1998 to 2002, many municipal water suppliers in the Piedmont/Blue Ridge areas of central Maryland (USA) had to institute water restrictions due to declining well yields. Previous estimates of the yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The latter study noted that caution should be placed when assigning sustainable yields to boreholes in aquifers characterised by fracture dewatering since it is dependent on the abstraction rate. Clogging of fractures due to calcite precipitation and fracture compaction were also associated with fracture dewatering in a study by Hammond (2018), and this resulted to reduction of yield by 40-50%. Khan et al (2020) indicated that dewatering influences total dissolved solids interactions through rock-water interaction especially in aquitard and aquifer rich fine sediments (clay, carbonate and hard rocks).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter study noted that caution should be placed when assigning sustainable yields to boreholes in aquifers characterised by fracture dewatering since it is dependent on the abstraction rate. Clogging of fractures due to calcite precipitation and fracture compaction were also associated with fracture dewatering in a study by Hammond (2018), and this resulted to reduction of yield by 40-50%. Khan et al (2020) indicated that dewatering influences total dissolved solids interactions through rock-water interaction especially in aquitard and aquifer rich fine sediments (clay, carbonate and hard rocks).…”
Section: Discussionmentioning
confidence: 97%
“…Leaky aquifer models provided best matches of estimated and recorded drawdown data than any other solutions in the basement aquifers in Ethiopia in a study by Daddi (2015). Leakage conditions was also identified by Hammond (2018) as one of the dominant flow regimes based on analysis of hydraulic tests data in the fractured-rock aquifers of central Maryland, United States of America. Holland (2011) also noted that crystalline basement rocks are usually semiconfined (fractured bedrock).…”
Section: Discussionmentioning
confidence: 99%
“…More robust techniques, such as geophysical profiling, for example, thermal, sonic, optical profiling, etc. (Danielsen et al 2007;Fiume et al 2020), as well as more traditional techniques, such as field mapping (Gleeson and Novakowski 2009;Fernandes et al 2016) and well monitoring (Comte et al 2012;Hammond 2018) are important to improve the conceptual model of the aquifer, however this study aims to make an initial contribution to the region's crystalline aquifer, in a regional and remote way, using, therefore, investigative techniques that will serve as a basis in the future for further studies in greater detail such as outcrop analysis, geophysical profiling and hydraulic well monitoring. In this sense, we address in this study the location of the wells and their production values, and the remote sensing mapping of outcropping structures in the relief and magnetized structures, associating these mapped structures and the wells with the spatial distribution of the lithologies and the tectonic context past and current of Paraná's crystalline basement.…”
Section: Introductionmentioning
confidence: 99%
“…Published approaches to quantifying individual borehole yields in fractured rocks during drought periods are scant. Individual case studies have been reported in the USA (Hammond, 2018), UK (Beeson et al, 1997), South Africa (van Tonder et al, 2001), Italy (Piscopo and Summa, 2007) and…”
mentioning
confidence: 99%
“…Even in countries with well-developed water resources management practices, estimates of borehole yields during droughts have been shown to be substantially overestimated (Hammond, 2018). Methods for estimating groundwater yields are often not reported and in areas of conjunctive water distribution borehole yields are combined with surface water yields to derive a total yield for the water resource system (UK Water Industry Research Ltd, 2014).…”
mentioning
confidence: 99%